Lithostratigraphy and chemostratigraphy of Triassic black shales on Edgeøya, eastern Svalbard: Implications for understanding Triassic source rock formation on the Norwegian Barents Shelf - Wesenlund, Fredrik (UiT Norges arktiske universitet, 2022)
The Norwegian Barents Shelf (NBS) is an Arctic petroleum province with a complex geological history. Current geochemical work on oil discoveries in the region has identified Triassic mudstones as important petroleum source rocks. A review of the published literature found that several source rock-forming processes have been suggested as contributors to their formation. The aim of this thesis is thus to further understand the paleoenvironmental factors that affected Triassic source rock formation and potential on the NBS. This was done by investigating the lithostratigraphy and organic/inorganic chemostratigraphy of the organic-rich Spathian–Carnian outcrops on Edgeøya, eastern Svalbard. These exposures represent uplifted and exhumed strata of the northwestern NBS that are equivalent to Triassic source rocks on the southern NBS. Paper I characterizes the mudstone facies and bulk organic properties of the Anisian–Ladinian Botneheia Formation to investigate benthic redox conditions, productivity, and organic richness. Paper II performs a multi-elemental chemostratigraphic analysis to further clarify how these environmental factors affected Spathian–Carnian source rock formation. Paper III documents source- and maturity-specific biomarker compounds of the investigated succession and their correlation with oils from the Alta, Gohta, Wisting Central and Hanssen discoveries on the NBS. These papers consider the reported climate-induced transition from warmer to cooler oceans at the Spathian–Anisian boundary to have an important impact on Spathian vs. Anisian–Ladinian source rock formation in the region. The early Carnian pro-deltaic mudstones terminated formation of oil-prone source rocks due to the prograding Triassic Boreal Ocean delta system in the south. Spathian mudstone extracts from Svalbard and the Spathian-sourced Wisting Central/Hanssen oils show strong biomarker correlations, indicating that these age-equivalent source rocks have comparable organic facies. This challenges the idea that Spathian mudstones on ...